Riesgos del arco eléctrico en el sistema de puesta a tierra de subestaciones eléctricas - Flores Carpio, Jackson Francisco (2023)
Every person who performs work using energized equipment or energized lines is faced with a latent danger that is permanently present during the development of their activities. The electric arc is one of these dangers, and the object of analysis in the present research work. The arc-flash can cause serious injuries to a person even without having contacted energized parts of the equipment. The incident current, step currents and touch current are analyzed, as well as the safety distances and categories of personal protection equipment according to the NFPA 70E, IEEE 1584, and IEEE 80 standards. Keywords: Arc-flash, security electric standards, NFPA, electric hazard.